Non-contact monitoring of grouper fry weaning in recirculating aquaculture systems: Efficacy of an automated stereo vision system - Cheng-Yuan Kuo; Rung-Chi Lin; Tzong-Yueh Chen; Pei-Ju Chiang (Aquacultural Engineering, 2027)

RMRP mediates neuroprotection as a downstream effector of RBM3 in human neuroblastoma SH-SY5Y cells - Shuangping Ma; Xianting Liu; Yiming Xie; Yuxuan Han; Ning Wang; Shenxue Li; Binfeng Cheng; Fei Ju; Lei Wang (Molecular Genetics and Genomics, 2026)

Decadal stability and forensic reliability of petroleum biomarkers in tropical coastal environments: Validating laboratory kinetics against 10-year field residues - Ying-Ju Chang; Cheng-Ting Lin (Marine Pollution Bulletin, 2026)

Macromolecular behavior and structural characteristics of β-glucans from different species on their noncovalent interactions with avenanthramide-C - Zicong Guo; Jiawei Cao; Jincheng Zhang; Chengjie Ren; Wentao Xu; Yongqiang Cheng; Zhigang Jiang; Jiangtao Zhou; Dejian Huang; Ju Qiu (Food Hydrocolloids, 2026)

Associations of urinary heavy metals and their mixture with sleep quality during pregnancy: A prospective study - Jiayi Song; Jiao Li; Kefeng Fan; Pengpeng Sun; Qian Sun; Shuang Cheng; Xiaohui Guo; Qi Li; Xiang Wang; Ju Wang (Journal of Trace Elements in Medicine and Biology, 2026)

Chain-length-dependent tissue biodistribution of polyethylene glycol oligomers with 9-20 subunits revealed by green UPC2-MS/MS - Xinyue Zhou; Jiale Liu; Hongjie Ju; Si Cheng; Shuang Feng; Yue Deng; Jiarui Zhang; Yalin Xi; Meiyun Shi; Lei Yin (Food Research International, 2026)

Emission of hazardous air pollutants in solid recovered fuel (SRF) industrial boilers and health risk assessment in the vicinity - Shih Yu Pan; Jung-Wei Chang; Hsin Ju Hsieh; Jing Min Duh; Hou Chuan Wang; Charles C.-K. Chou; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Pollution, 2026)

4-OI-preconditioned exosomes delivered by a ROS-responsive hydrogel promote spinal cord injury repair via immunomodulation and mitochondrial protection - Cheng Ju; Yuqi Zhao; Hui Dong; Renfeng Liu; Ruiqing Xu; Rongjin Luo; Dageng Huang; Liang Yan; Huimin Hu (Chemical Engineering Journal, 2026)

Electrochemical steering of syntrophic consortia in constructed wetlands: Dual benefits for nitrogen removal and antibiotic resistance risk control under chloramphenicol stress - Jiawei Xie; Liming Zhang; Xinyu Zhu; Lei Zhou; Weicong Wang; Shuangqi Wu; Chongjun Chen; Qiaohong Zhou; Feng Ju; Shuiping Cheng (Water Research, 2026)

Electronic structure engineering of 2D Ni-MOF/CNTs for glucose monitoring and energy supply in a wearable sweat sensor system - Rui-Dong Shi; Guo-Tao Xiang; Tao Cheng; Zi-Dong Zhou; Na Chen; Raul D. Rodriguez; Jin-Ju Chen (Chemical Engineering Journal, 2026)

Petrophysically Constrained ERT for Resolving Spatiotemporal Clogging Evolution in Sand Filtration Systems - Ho Wen Chen; Winn-Jung Huang; Chih Cheng Chang; Chien-Yuan Chen; Hsin-Chang Liu; Yu-Ju Chang (Environmental Processes, 2026)

Analysis of Electromagnetic Response Characteristics of Energized Subsea Cables in Complex Scenarios - Qi-feng Xiao; Cong Zhou; Min Feng; Cheng-hong Miao; Ju-zhi Deng; Shao-dong Zhang (Applied Geophysics, 2026)

Real-world safety of aflibercept 8 mg in neovascular age-related macular degeneration - Wan-Ju Annabelle Lee; Daniel Hsiang-Te Tsai; Edward Chia-Cheng Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Enhancing vertical and temporal allocation of freeway traffic emissions to improve air quality modeling in Taiwan - Yi-Ju Lee; Fang-Yi Cheng; Bo-Sheng Huang; Sheng-Po Chen (Environmental Pollution, 2026)

A flexible antigen-presenting cell targeting lentinan immunomodulator promotes stimulator of interferon gene-driven cancer therapy - Jiaqian Miao; Junjie Wang; Qianli Zhu; Xiangshu Cheng; Jingxuan Ju; Minxia Zhang; Jiaxuan Guo; Li Xu; Guangbo Ge; Mingming Jin; Hongping Deng (Carbohydrate Polymers, 2026)

Comment: Plasma as the Extracellular Matrix of Platelets—Rethinking the Mechanistic Basis of PRP Therapy - Ju Tian; Jing Ding; Haixia Wang; Xiaoying He; Dandan Shi; Biao Cheng (Stem Cell Reviews and Reports, 2026)

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

A coupled numerical model for dynamic response and wake analysis of a floating tidal turbine system in waves and currents - Mengqi Cheng; Ju Fan; Zhen Gao; Yuzhu Pearl Li (Ocean Engineering, 2026)

Mitigating strainburst in roadways using segmented variable-diameter destressing boreholes: An investigation into zonal fracture response - Ruyi Cheng; Minghe Ju; Liyuan Yu; Lianpeng Dai; Tao Zhang; Lihua Hu; Minjie Ding; Yuxuan Peng (International Journal of Rock Mechanics and Mining Sciences, 2026)

Impact of high-pressure processing on the degradation kinetics and bioactivity of resveratrol - Wen-Chien Lu; Yu-Tsung Cheng; Yung-Jia Chan; Shu-Ju Chen; Yan-Zhen Wu; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Non-enzymatic electrochemical determination of the food-related biogenic amine serotonin using a reduced graphene oxide/organic–inorganic Copper(I) phosphate composite - Asit Kumar Panda; Tzu-Yuan Sung; Wan-Ju Lu; Yi-Ru Cheng; Wen-Hui Fang; Chih-Min Wang (Food Bioscience, 2026)

Quercetin-lysozyme complex as a novel wall material for microencapsulation of DHA algal oil: Molecular Dynamics、Structural characterization and antioxidant capacity - Lili Liu; Shuhang Ju; Dan Li; Weiwei Cheng; Xinshuai Zhang; Li Hu (Food Bioscience, 2026)

Mechanism of Pre-tensioned Bolt for Strainburst Mitigation: Insights from the Regulation of Stress/Energy Fields and Fracture Pattern - Ruyi Cheng; Minghe Ju; Liyuan Yu; Yang Zou; Hao Ji; Bo Zhang; Minjie Ding; Xiaofeng Li (Rock Mechanics and Rock Engineering, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

Dynamic response of monopile offshore wind turbines in cement-improved clay under seismic and environmental loads - Xinglei Cheng; Zeyang Zhang; Chao Ma; Lei Liu; Ju Liu; Xiaohan Sun (Ocean Engineering, 2026)

More neighborhood green space, fewer park visits? Evidence from mobile phone-based population movement data in a major Chinese city - Shicheng Wen; Tianyuan Shou; Hao Song; Xize Wang; Haiwei Yin; Yingyi Cheng; Guanghua Sun; Yang Ju (Journal of Transport Geography, 2026)

Associations between metal mixture exposure and emotional distress symptoms among pregnant women: A prospective study - Qi Li; Jiao Li; Shuang Cheng; Xiaohui Guo; Jiao Liu; Hongyue Dai; Ju Wang (Journal of Trace Elements in Medicine and Biology, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

The NH4+–N adsorption performance regulated by the external surface of water storage clay: Particle size effect and path analysis - Xiaolan Ju; Cheng Wu; Juanjuan Ma; Lijian Zheng; Xihuan Sun (Environmental Research, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

A cleaner production strategy for coalbed methane extraction: Enhancing coal permeability through sodium persulfate oxidation - PengCheng Zhang; Haihui Xin; Jinfeng Wu; Huihui Liu; Shaoting Ju; GuoQing Shi; Bekir Genc; Cheng Zhai (Fuel, 2026)

Microenvironment-responsive exosomes-hydrogel hybrid system for inflammation modulation and neural regeneration after spinal cord injury - Cheng Ju; Yanming Ma; Renfeng Liu; Yuqi Zhao; Shenghang Liu; Hui Dong; Ruiqing Xu; Rongjin Luo; Lei Zhu; Huimin Hu (Chemical Engineering Journal, 2026)

Sweat-responsive natural small-molecule-based co-assembled hydrogels: multifunctional properties, transdermal delivery, and potential for hyperhidrosis therapy - Mingping La; Jiamei Le; Chunxia Yin; Pan Cheng; Fen Ju; Xiaohong Zhu; Cui Li (Chemical Engineering Journal, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Machine Learning Approaches for Probabilistic Prediction of Coastal Freak Waves - Dong-Jiing Doong; Wei-Cheng Chen; Fan-Ju Lin; Chi Pan; Cheng-Han Tsai (Journal of Marine Science and Engineering, 2026)
Coastal freak waves (CFWs) are sudden and hazardous wave events that occur near shorelines and can pose serious threats to coastal visitors and infrastructure. Due to the complex interactions among coastal bathymetry, wave dynamics, and environmental conditions, the mechanisms governing CFW formation remain poorly understood, making reliable prediction difficult. This study investigates the feasibility of applying machine learning techniques to predict CFW occurrences using observational environmental data. Three machine learning algorithms, the Random Forest (RF), Support Vector Machine (SVM), and Artificial Neural Network (ANN), were developed to generate probability-based predictions of CFW events. Environmental variables derived from buoy observations, including wave characteristics, wind conditions, swell parameters, wave grouping indicators, and nonlinear wave interaction indices, were used as model inputs. Hyperparameters were optimized using grid search combined with k-fold cross-validation. The results show that all three models achieved comparable predictive performance, with AUC values close to 0.80 and overall prediction accuracy around 74%. The ANN model achieved the highest recall, indicating strong capability in detecting CFW events, while the RF and SVM models showed more balanced precision and recall. Analysis of high-probability prediction events suggests that CFW occurrences are associated with swell-dominated conditions, strong wave grouping behavior, and enhanced nonlinear wave interactions. These results demonstrate that machine learning provides a promising framework for probabilistic prediction of coastal freak waves and has potential applications in coastal hazard assessment and early warning systems.

Data fusion for fine-scale ozone mapping in the New York City metropolitan area using low-cost sensors and model information - Ellie Hojeily; Cheng-Hsuan Lu; Stefano Alessandrini; Ju-Hye Kim; Rajesh Kumar; Shih-Wei Wei; Liam Sheji; Md. Aynul Bari; Scott D. Miller (Atmospheric Environment, 2026)

Analysis of the “South-High North-Low” phenomenon of aerosol distribution and its characteristics in the Beijing plain area - Jie Su; Ju Li; Jingjiang Zhang; Junxia Dou; Youjun Dou; Shaoying Shi; Yaoting Wang; Yao Wang; Zhigang Cheng; Wenlong Zhang (Atmospheric Pollution Research, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Boosting ammonia-fed solid oxide fuel cell performance via high-entropy alloy anode surface modification - Nasima Khatun; Cheng-Ju Lin; Jia-You Lin; Sridharan Balu; Shi-Shin Yang; Sea-Fue Wang; Thomas C.-K. Yang (Fuel, 2026)

Intraocular inflammation incidence and real-world safety of intravitreal faricimab treatment across retinal indications - Wan-Ju Annabelle Lee; Daniel Hsiang-Te Tsai; Shih-Chieh Shao; Edward Chia-Cheng Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

A 24-year record of Cetacean strandings in Taiwanese waters: Signals of escalating threats - Yun Ho; Lien-Siang Chou; Chiou-Ju Yao; Wei-Lien Chi; Hao-Ven Wang; Ing Chen; Hsin-Yi Yu; Pei-Ying Wu; Wei-Cheng Yang (Marine Environmental Research, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Model-Dependent Attenuation of Seizures by Cinnabar - Yuang Gu; Yu Yao; Qiuwen Lou; Xinyan Zhu; Ju Lan; Chenshu Gao; Shuangshuang Wu; Jingjia Liang; Cenglin Xu; Yi Wang; Heming Cheng; Zhong Chen (Neuroscience Bulletin, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Nitrate dynamics in engineered plain polder–river networks driven by surface water–groundwater interactions - Shenhao Qu; Dongli She; Yongchun Pan; Menghua Xiao; Peng Chen; Junhan Zhao; Taohong Cao; Xinni Ju; Li Zhang; Cheng Lu; Yongqiu Xia (Journal of Hydrology, 2026)

Multiscale simulation of SiO2 nanoparticle evolution in coaxial premixed combustion reactors - Jie Ju; Lingli Luo; Yingjie Wu; Qilin Cheng; Hao Jiang; Yanjie Hu; Chunzhong Li (Chemical Engineering Journal, 2026)

3-n-Butylphthalide Protects SH-SY5Y Cells from Ferroptosis by Inhibiting ACSL4-Mediated Lipid Peroxidation - Huanhuan Wei; Yiyin Zhang; Qianqian Ju; Bolin Lian; Tong Gao; Haiqin Duan; Xiang Yin; Yongqi Lin; Jianhong Shen; Qiuhong Ji; Cheng Sun; Lihua Shen (Molecular Neurobiology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Spirocyclic polyketide analogues from the endophyte fungus Penicillium sp. YUD25002 associated with Panax notoginseng - Wen-Jing Wang; Ju-Cheng Zhang; Yan Geng; Hai-Xia Dong; Fei Xie; Tian-Peng Xie; Zhi-Feng Zi; Dan-Dan Xia; Han-Jue Zhang; Hao Zhou; Min Yin; Zhong-Tao Ding (Phytochemistry Letters, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Integrated analysis of internal moisture diffusion and surface moisture evaporation in the surface hardening phenomena of yam slices - Cheng Zhang; Zelan Wang; Bing Tian; Jiaqi Liu; Weipeng Zhang; Haoyu Ju; Weiqiao Lv; Hongwei Xiao (Food Research International, 2025)

Air pollutants, temperature, and road traffic noise: their impact on chronic kidney disease incidence in older individuals in Taiwan - Ting-Yu Zhuang; Wan-Ju Cheng; Yun-Chieh Yang; Chih-Cheng Hsu; Ta-Yuan Chang (Environmental Research, 2025)

Late deglacial and Holocene vegetation and climate change at Lake Mapam Yumco, southwestern Tibetan Plateau - Sima Humagain; Xinmiao Lü; Liping Zhu; Qingfeng Ma; Junbo Wang; Jianting Ju; Shaohang Zhu; Jiuju Cheng; Binija Kaphle; Khum Narayan Paudayal (CATENA, 2025)

Omega-3 polyunsaturated fatty acids ameliorate high-fat-diet-induced structural and functional impairments of testicular tissue via ER stress inhibition - Jiaxi Ju; Shuangli Wen; Xuan Zhao; Jiyuan Cheng; Hongjin Yang; Guiming Zhu (Transgenic Research, 2025)

Analysis of hydraulic response characteristics of reservoir bank slope under the action of reservoir water level rise and fall - Shu-Jun Ju; Ming-Li Xie; Neng-Pan Ju; Liang Duan; Ming-Cheng Jiang; Yu-Feng He (Applied Geophysics, 2025)

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Enhanced catalytic degradation of sulfamethazine by magnetic N-doped biochar: Performance evaluation and mechanism insight - Mengcan Ju; Lili Yan; Zhiwen Cheng; Tiantian Li; Guanghui Li; Pinhua Rao; Qincheng Chen; Benjiao Huo (Process Safety and Environmental Protection, 2025)

Deciphering structuring mechanism and increased health risk of antibiotic resistome from a coastal river basin to the downstream estuary and bay under anthropogenic disturbances - Xinyu Huang; Yuanzhen He; Lu Zhang; Jia Chen; Guoqing Zhang; Zhiguo Zhang; Wei Huang; Lukuo Ma; Fangping Cheng; Yuntao Wang; Xinyu Zhu; Feng Ju (Journal of Hazardous Materials, 2025)

A performance improving method of preparing nonlinear conductive coating for HVDC insulator based on plasma treatment technology: For lower-additive amounts and higher adhesive stability - Zijun Pan; Jiaming Cheng; Quanyou Nie; Zirui Wu; Yujie Qiu; Yuhan Ye; Shiyi Mao; Pu Han; Cheng Pan; Ju Tang (Chemical Engineering Journal, 2025)

Growing threat of climate-induced abrupt dry-wet transitions in Northern China - Cheng Ji; Evgenios Agathokleous; Lei Ju; Zhiwei Yu; Xiaorui Zhu; Tong Jiang; Buda Su; Guojie Wang; Sheying Tao; Lijuan Miao; Shao Sun; Qiang Liu (Atmospheric Research, 2025)

Association between novel agents targeting proprotein convertase subtilisin/kexin type 9 and cancer incidence - Hsueh-Ju Lu; Shiow-Ing Wang; Wei-Shiou Huang; Frank Sheng Fan; James Cheng-Chung Wei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

The new analogues of β - trans -bergamotene from endophytic fungus Nigrospora sp. E121 with yam culture medium - Ju-cheng Zhang; Xue-qiong Yang; Hao Zhou; Ya-Bin Yan; Zhong-tao Ding (Natural Product Research, 2025)

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Quantifying tree-level peach flowering dynamics using UAV imagery and an optimized instance segmentation model - Qing Gu; Jiayu Cheng; Minghao Zhang; Xiongwei Li; Robert Jackson; Lei Ju; Weidong Lou; Miaojin Chen; Ji Zhou; Xiaobin Zhang (Computers and Electronics in Agriculture, 2025)

Calibration of the Edinburgh Elasto-Plastic Adhesion contact model for modelling clay-moist soil with high moisture content - Xuan Deng; Wencheng Wu; Jiawei You; Rui Jiang; Mengliang Li; Ju Li; Youfeng Tao; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; et al. (Computers and Electronics in Agriculture, 2025)

Dual-functional geopolymers from industrial and agricultural wastes for copper adsorption and sustainable construction applications - Tee Hoe-Woon; Heah Cheng-Yong; Liew Yun-Ming; Ng Qi-Hwa; Lee Wei-Hao; Darshinder Supramanian; Lim Jia-Ni; Yip Yu-Xin; Liu Mei-Ju (Journal of Environmental Chemical Engineering, 2025)

Elucidating the interplay between pore microstructure and heavy metal leaching of rubber sludge in fly ash geopolymers - Tee Hoe-Woon; Heah Cheng-Yong; Liew Yun-Ming; Ng Qi-Hwa; Lee Wei-Hao; Foo Kai Loong; Phakkhananan Pakawanit; Darshinder Supramanian; Lim Jia-Ni; Yip Yu-Xin; Ong Shee-Ween; Liu Mei-Ju (Journal of Environmental Chemical Engineering, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Study on the reaction mechanism of nitrogen-containing gases from polyurethane pyrolysis with carbonate molten salts - Yang-Hai Zheng; Jun-Qiang Rui; Sheng-Rong Guo; Cheng Yao; Zhao-Yang Liu; Yun Xue; Ju-Yue Yang; Yong-De Yan (Fuel, 2025)

Ultrarobust eutectogels with nanophase separation structure for self-damping pressure sensing - Zong-Ju Chen; Yu-Qiong Sun; Zi-Han Zhao; Li-Jia Pan; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Fully conformal wrapping of N,S co-doped carbon nano-wrinkles on graphene matrix for flexible and wearable supercapacitors - Fei Liu; Guoxiang Xin; Teng Ju; Yutong Cheng; Haitao Wang; Jinxiao Bao; Qingchun Wang; Jinling Song; Guangshu Sun (Chemical Engineering Journal, 2025)

Biofilm-enhanced PFAS removal in constructed wetlands: Sewage sludge biochar drives adsorption and microbial synergy - Fuhao Zhang; Cheng Shen; Yaqian Zhao; Lingwei Kong; Feng Ju; Bin Ji; Yu Bon Man; Shengdao Shan; Yuliang Li; Jin Zhang (Chemical Engineering Journal, 2025)

High-entropy sulfide and nanozyme hybrid system with synergistic interface-engineering: Ultra-sensitive photoelectrochemical detection of chloramphenicol - Yi-Hong Chen; Ai-Jun Wang; Ya-Cheng Shi; Li-Ping Mei; Pei Song; Tiejun Zhao; Jiu- Ju Feng (Chemical Engineering Journal, 2025)

Responses of anuran diversity and community structure to an urbanization gradient in a subtropical Asian city - Yung-Chih Lai; Cheng-En Li; Wei-Chun Cheng; Tien-Chen Lai; Pei-Fen Lee; Yi-Ju Yang (Urban Ecosystems, 2025)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Contrasting Pacific Decadal Oscillation influence on ice core dust deposition across the Tibetan Plateau - Cheng Wang; Lide Tian; Zhongyin Cai; Lili Shao; Ju Huang; Rong Li; Chenhao Xu; Zixiang Zhao (Quaternary Science Reviews, 2025)

Unlocking plateau capacity of coal-derived hard carbon with tailored microcrystal structure via induced-catalytic engineering for sodium-ion batteries - Fengcui Cheng; Meiyun Wang; Zhicheng Ju; Jiangmin Jiang; Yaowen Xing; Xiahui Gui (Chemical Engineering Journal, 2025)

The functions of international adjudication and international environmental litigation, by Joshua Paine, Cambridge university press, 2024, 370 Pp, $ 135 Hb, ISBN 9781108493499 - Shuji Ju; Le Cheng (International Environmental Agreements: Politics, Law and Economics, 2025)

Mulberroside A ameliorates murine allergic airway inflammation by suppressing Th2 response and oxidative stress - Chian-Jiun Liou; Shu-Ju Wu; Shu-Chen Cheng; Wen-Chung Huang (Inflammopharmacology, 2025)

Energy evolution characteristic and fracturing mechanism of roadway soft rock under multilevel static-dynamic coupling disturbance loading - Ruyi Cheng; Hu He; Liyu Yu; Lihua Hu; Minghe Ju; Dongyang Wu (Bulletin of Engineering Geology and the Environment, 2025)

Efficient prediction of gaseous n-hexane removal in two-phase partitioning bioreactors with silicone oil based on the mechanism and kinetic models - Lichao Lu; Tuo Ju; Yangdan Fang; Jingtao Hu; Zhuqiu Sun; Zhuowei Cheng; Qian Li; Jianmeng Chen; Dong-zhi Chen (Journal of Environmental Sciences, 2025)

Chemical characterization and oxidative potential of persistent organic pollutants (POPs) in size-resolved particulate matter across industrial and traffic stations - Shahzada Amani Room; Po Jui Chen; Zhi Yu Chen; Yu Ju Shih; Shih Yu Pan; Yuan-Cheng Hsu; Ta-Chih Hsiao; Yu Chieh Ting; Charless C.-K Chou; Chien-Hou Wu; Kai Hsien Chi (Environmental Research, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

The nematicidal activity of Bacillus thuringiensis Cry1Ia36 expressing in Escherichia coli - Feixue Cheng; Dongwei Wang; Jian Wang; Xin Wang; Minzhi Long; Shu-e Sun; Chunhui Zhu; Ju-e Cheng; Xinqiu Tan; Deyong Zhang; Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Mechanism and kinetics of microwave-enhanced disposal of Zn-bearing dust using petroleum coke - Haiming Cheng; Zhuo Chen; Tingfeng Yao; Guangqiang Pu; Dianchun Ju; Weitong Du (Journal of Environmental Chemical Engineering, 2025)

In-situ generation of Ni component through interface engineering of NiO/graphene composite for high-performance supercapacitor - Guoxiang Xin; Fei Liu; Teng Ju; Yutong Cheng; Jinxiao Bao; Wei Sun; Jinling Song; Chaoke Bulin (Chemical Engineering Journal, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

Combination of NRPS/PKS tuning and morphological engineering enhanced iturin A production in Bacillus amyloliquefaciens - Zheng-Jie Hou; Hai-Meng Lai; Kai-Ge Song; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Correction to: Influence of Synoptic Pattern on the Spatiotemporal Features and Diurnal Variation of Extremely Persistent Heavy Rainfall over the Sichuan Basin, China - Fan Xia; Xiaogang Huang; Jianfang Fei; Ju Wang; Xiaoping Cheng; Chi Zhang (Advances in Atmospheric Sciences, 2025)

Multifunctional nanofiber aerogels for environmental applications: Oil water separation, thermal insulation, fire proofing - Heng Wang; Jie-Yu Xue; Yi-Yi Ju; Ying-Jun Gao; Xian-Wei Cheng; Jin-Ping Guan (Journal of Environmental Chemical Engineering, 2025)

Origins of the overestimated Indian Ocean dipole amplitude in current coupled climate models - Xiaoming Ju; Shangfeng Chen; Wen Chen; Renguang Wu; Lin Chen; Xin Cheng (Climate Dynamics, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Core-shell hydrogel microspheres with sequential delivery of cerium oxide nanoparticles and spinal white matter extracellular matrix for improved functional recovery in spinal cord injury - Yixiang Ai; Chunping Hu; Yifan Wang; Youjun Liu; Renfeng Liu; Hailiang Xu; Hui Li; Yuqi Zhao; Yuhao Wang; Ruojie Ning; Cheng Ju; Weidong Wu; et al. (Chemical Engineering Journal, 2025)

Distribution characteristics of microplastics in surface waters in the western Pacific Ocean - Cheng Huo; Shoufeng Zhang; Ling Qu; Shuaichen Jin; Cijia Wang; Xiaoting Chu; Maowei Ju (Journal of Oceanology and Limnology, 2025)

Influence of Synoptic Pattern on the Spatiotemporal Features and Diurnal Variation of Extremely Persistent Heavy Rainfall over the Sichuan Basin, China - Fan Xia; Xiaogang Huang; Jianfang Fei; Ju Wang; Xiaoping Cheng; Chi Zhang (Advances in Atmospheric Sciences, 2025)

Relationship between bubble motion, nitrogen removal, and microbial community characteristics in black-odorous water under micro-aeration: Effects of aeration rate - Cheng Lu; Wen Cheng; Bo Zhang; JiaXuan Wang; JieHui Ren; Kai Ju (Journal of Water Process Engineering, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Genetic Mechanism Analysis Related to Cold Tolerance of Red Swamp Crayfish, Procambarus clarkii - Jihu Zhang; Cheng-long Zhang; Hong Ju Chen; Xiang Shan Ji; Yan Zhao (Marine Biotechnology, 2025)

Correction to: Resveratrol Mitigates Cerebral Ischemic Injury by Altering Levels of Trace Elements, Toxic Metal, Lipid Peroxidation, and Antioxidant Activity - Ju-Hai Ro; Chien-Chi Liu; Ming-Cheng Lin (Biological Trace Element Research, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Corrigendum to “Hydrogen peroxide as a mitigation against Microcystis sp. Bloom” [Aquaculture, Volume 577, 15 December 2023, 739932] - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2025)

Geodetic constraints on the September 2022 Guanshan and Chihshang earthquakes, eastern Taiwan - Hsin Tung; Horng-Yue Chen; Ya-Ju Hsu; Chi-Hsien Tang; Jian-Cheng Lee; Yu Wang; Hung Kyu Lee (Tectonophysics, 2025)

Exploring the inhibitory activity and mechanism on lipid production in 3T3-L1 cells by hot water extract derived from Acacia confusa flowers - Nai-Wen Tsao; Ju-Ya Cheng; Sheng-Yang Wang (Journal of Natural Medicines, 2025)

Protective Effects of Antcin H Isolated from Antrodia cinnamomea Against Neuroinflammation in Huntington’s Disease via NLRP3 Inflammasome Inhibition - Yu-Jun Chang; Cheng-Hsu Chen; Yi-Chen Chen; Ming-Tse Wu; Ting-Yu Lin; Kuo-Feng Hua; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2024)

Development of a regional carbon assimilation system and its application for estimating fossil fuel carbon emissions in the Yangtze River Delta, China - Zhengqi Zhang; Shuzhuang Feng; Yan Chen; Qiang Liu; Weimin Ju; Wei Xiao; Cheng Huang; Yanyu Wang; Hengmao Wang; Mengwei Jia; Xingyu Wang; Fei Jiang (Science of The Total Environment, 2024)

Capturing differences in the release potential of dissolved organic matter from biochar and hydrochar: Insights from component characterization and molecular identification - Rongting Ji; Yiting Yang; Yudong Wu; Changyin Zhu; Ju Min; Chenwei Liu; Longjiang Zhang; Hu Cheng; Jianming Xue; Dongmei Zhou (Science of The Total Environment, 2024)

Manganese(III) dominants the mobilization of phosphorus in reducing sediments: Evidence from Aha reservoir, Southwest China - Quan Chen; Jing-fu Wang; Meng-qiang Zhu; Hai-bo Qin; Peng Liao; Zhi-tong Lu; Peng-cheng Ju; Jing-an Chen (Science of The Total Environment, 2024)

Petrogenesis of the Zenong Group volcanics in the central Lhasa subterrane, Tibet: Geodynamic implications of the scissor-like southward subduction of the Shiquanhe-Jiali Tethyan Ocean - Jia-jia Yu; Wei Chen; Ju-Xing Tang; Cheng-Yang Wang; Xu-Dong Ma; Qing-Ping Liu; Meng-Xiang Di; Chang Liu (Lithos, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

Enhancing real-time PM2.5 forecasts: A hybrid approach of WRF-CMAQ model and CNN algorithm - Yi-Ju Lee; Fang-Yi Cheng; Hsiao-Chen Chien; Yuan-Chien Lin; Min-Te Sun (Atmospheric Environment, 2024)

Can new-type urbanization construction policy mitigate energy consumption intensity? Evidence from Chinese listed enterprises - Cheng Ju; Can Yuan; Jiale Yan; Cem Işık (Environment, Development and Sustainability, 2024)

Structural behavior and strength of randomly pitted steel T-joints with circular hollow sections - Renhua Wang; Yizhe Li; Jianjun Ju; Shanshan Cheng (Ocean Engineering, 2024)

Investigation of the nitrogen reduction mechanism in black-odorous water by micro-aeration and its correlation with microorganism population characteristics: The aeration-cessation time ratio factor - Cheng Lu; Bo Zhang; Shengnan Zhou; Wen Cheng; JiaXuan Wang; Kai Ju (Journal of Water Process Engineering, 2024)

Research on fault diagnosis of electric gate valve in nuclear power plant based on the VMD-MDI-ISSA-RF model - Jia-rong Gao; Yong-kuo Liu; Cheng-jie Duan; Peng Ding; Ju-qing Song (Annals of Nuclear Energy, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Relationship between human activities and environmental changes in the southern Tibetan Plateau since the Little Ice Age - Cunlin Li; Liping Zhu; Qingfeng Ma; Jianting Ju; Jiuju Cheng; Marco A. Aquino-López; Run Zhang; Qiangqiang Kou; Xinmiao Lü; Junbo Wang (Science of The Total Environment, 2024)

Urinary concentrations of mineral elements and their predictors in pregnant women in Jinan, China - Xiaohui Guo; Jiayi Song; Xiang Wang; Qichen Huang; Chuanling Wei; Yujie Yang; Nan Li; Shuang Cheng; Jiao Li; Qi Li; Ju Wang (Journal of Trace Elements in Medicine and Biology, 2024)

Incense-burning smoke ingredient Auramine enhances lincRNA-p21 expression for chemosensitization in p53-mutated non-small cell lung cancer - Hsuan-Yu Huang; Chia-Hung Chen; Fang-Ju Cheng; Bo-Wei Wang; Chih-Yen Tu; Yun-Ju Chen; Yu-Hao He; Chun-Hsu Yao; Wei-Chien Huang (Journal of Hazardous Materials, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Modelling the distribution of fish habitat type and habitat diversity in natural rivers - Hsuan-Ju Hung; Wei-Cheng Lo; Ching-Nuo Chen; Chih-Heng Tsai (Journal for Nature Conservation, 2024)

Photobiomodulation Increases M2-Type Polarization of Macrophages by Inhibiting Versican Production After Spinal Cord Injury - Zhi-Hao Zhang; Ting-Yu Wu; Cheng Ju; Xiao-Shuang Zuo; Xuan-Kang Wang; Yang-Guang Ma; Liang Luo; Zhi-Jie Zhu; Zhi-Wen Song; Zhou Yao; Jie Zhou; Zhe Wang; et al. (Molecular Neurobiology, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Exploring the optimal integrated multi-trophic aquaculture (IMTA) patterns benefiting culture animals and natural water environment - Yongtao Tang; Chenxi Ju; Ruigang Mei; Liangjie Zhao; Jun Liu; Yang Yang; Xusheng Guo; Chaoqun Su; Yongxu Cheng; Qigen Liu (Aquaculture, 2024)

The effects and mechanisms of heat stress on mammalian oocyte and embryo development - L.I. Lang; Zhen-zhen Wang; Bin Liu; S.H.E.N. Chang-qing; T.U. Jing-yi; W.A.N.G. Shi-cheng; L.E.I. Rui-ling; P.E.N.G. Si-qi; X.I.A.O. Xiong; Z.H.A.O. Yong-ju; Xiao-yan Qiu (Journal of Thermal Biology, 2024)

Pyrolysis-free coupling strategy to synthesize two-dimensional oxygen reaction electrocatalysts for rechargeable Zn-air batteries - Peng-Fei Xie; Hao Hu; Lingzhe Fang; Xiaohua Yu; Ju Rong; Xiaoyi Qiu; Feng Wu; Tao Li; Minhua Shao; Jin-Cheng Li (Chemical Engineering Journal, 2024)

A yarn-based sweat-activated battery constructed with conjugated electrospun nanofiber separators as a durable and high-capacity power source in textile electronics - Yanling Zheng; Huijun Sun; Yanjun Cheng; Wenhu Gao; Chenyu Wang; Jun Ju; Min Li; Xuemei Xiang; Wei Sun; Wei Wang; Zhisong Lu; Yan Qiao (Chemical Engineering Journal, 2024)

Fluvoxamine Exerts Sigma-1R to Rescue Autophagy via Pom121-Mediated Nucleocytoplasmic Transport of TFEB - Chun-Yu Lin; Hsiang-En Wu; Eddie Feng-Ju Weng; Hsuan-Cheng Wu; Tsung-Ping Su; Shao-Ming Wang (Molecular Neurobiology, 2024)
Expansion of the GGGGCC-RNA repeat is a known cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), which currently have no cure. Recent studies have indicated the activation of Sigma-1 receptor plays an important role in providing neuroprotection, especially in ALS and Alzheimer’s disease. Nevertheless, the mechanisms underlying Sigma-1R activation and its effect on (G 4 C 2 )n-RNA-induced cell death remain unclear. In this study, we demonstrated that fluvoxamine is a Sigma-1R agonist that can increase chaperone activity and stabilize the protein expression of Pom121 in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells, leading to increased colocalization at the nuclear envelope. Interestingly, fluvoxamine treatment increased Pom121 protein expression without affecting transcription. In C9orf72 -ALS, the nuclear translocation of TFEB autophagy factor decreased owing to nucleocytoplasmic transport defects. Our results showed that pretreatment of NSC34 cells with fluvoxamine promoted the shuttling of TFEB into the nucleus and elevated the expression of LC3-II compared to the overexpression of (G 4 C 2 ) 31 -RNA alone. Additionally, even when used alone, fluvoxamine increases Pom121 expression and TFEB translocation. To summarize, fluvoxamine may act as a promising repurposed medicine for patients with C9orf72 -ALS, as it stabilizes the nucleoporin Pom121 and promotes the translocation of TFEB in (G 4 C 2 ) 31 -RNA-expressing NSC34 cells.

Correction: Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)

Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)
Age-related macular degeneration (AMD) is a common retinal neurodegenerative disease among the elderly. Neovascular AMD (nAMD), a leading cause of AMD-related blindness, involves choroidal neovascularization (CNV), which can be suppressed by anti-angiogenic treatments. However, current CNV treatments do not work in all nAMD patients. Here we investigate a novel target for AMD. Granzyme B (GzmB) is a serine protease that promotes aging, chronic inflammation and vascular permeability through the degradation of the extracellular matrix (ECM) and tight junctions. Extracellular GzmB is increased in retina pigment epithelium (RPE) and mast cells in the choroid of the healthy aging outer retina. It is further increased in donor eyes exhibiting features of nAMD and CNV. Here, we show in RPE-choroidal explant cultures that exogenous GzmB degrades the RPE-choroid ECM, promotes retinal/choroidal inflammation and angiogenesis while diminishing anti-angiogenic factor, thrombospondin-1 (TSP-1). The pharmacological inhibition of either GzmB or mast-cell degranulation significantly reduces choroidal angiogenesis. In line with our in vitro data, GzmB-deficiency reduces the extent of laser-induced CNV lesions and the age-related deterioration of electroretinogram (ERG) responses in mice. These findings suggest that targeting GzmB, a serine protease with no known endogenous inhibitors, may be a potential novel therapeutic approach to suppress CNV in nAMD.

Anti-aging effects of dietary phytochemicals: From Caenorhabditis elegans , Drosophila melanogaster , rodents to clinical studies - Ju-Chi Chen; Reuben Wang; Chia-Cheng Wei (Critical Reviews in Food Science and Nutrition, 2024)

Predictors of urinary heavy metal concentrations among pregnant women in Jinan, China - Jiayi Song; Xiang Wang; Qichen Huang; Chuanling Wei; Dongxia Yang; Cuilan Wang; Kefeng Fan; Shuang Cheng; Xiaohui Guo; Ju Wang (Journal of Trace Elements in Medicine and Biology, 2024)

In vitro and silico studies of geraniin interfering with HSV-2 replication by targeting glycoprotein D - Hao Zhang; Liang Cheng; Feng Ju (Natural Product Research, 2024)

Physicochemical properties of Dioscorea alata Tainung No. 1 and 2 via different drying methods and application on the frozen tangyuan - Ping-Hsiu Huang; Yu-Tsung Cheng; Shu-Ju Chen; Wen-Chien Lu; Po-Yuan Chiang; Wen-Pei Cheng; Chiun-Chuang R. Wang; Po-Hsien Li (Food Bioscience, 2024)

Regulating and protecting of oxygen vacancy endow MoO3-x@Zn2In2S5 S-scheme core–shell heterojunction with high-efficiency organic pollutant removal and bacterial disinfection: Correlation of pollutant active sites to degradation pathways - Ya-Ya Yang; Hao-Peng Feng; Xue-Gang Zhang; Hai Guo; Xiao-Ju Wen; Long Sui; Zheng-Tao Dong; Ming Yan; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

Preventive effects of Ramelteon on bleomycin-induced pulmonary fibrosis in mice - Lei Zhang; Ting Cheng; Wenxian Chen; Changsheng Zhong; Mengyang Li; Yilin Xie; Qin Deng; Huifang Wang; Zhenbo Yang; Jin Ju; Haihai Liang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Study on the dispersion stability of kaolin in oil phase - Chao Li; Tie Geng; Ju Huang; Cheng Zhang; Ming Duan; Shenwen Fang; Xinliang Li; Shuai Liu (Applied Clay Science, 2024)

Micro-level stress characteristics of rapeseed particle during the seeding process using the MFBD-DEM coupled method - Wencheng Wu; Xuan Deng; Ju Li; Jianfeng Hu; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; Xiaolong Lei (Computers and Electronics in Agriculture, 2024)

Analysis of human health effects under ozone exposure in the oasis area of Hetao Plain - Lanzhi Wang; Tianzhen Ju; Bingnan Li; Xuhui Xia; Cheng Huang; Zhichao Lv; Zhenrong Gu (Environmental Monitoring and Assessment, 2024)

Joint improvement on absorbed photosynthetically active radiation and intrinsic quantum yield efficiency algorithms in the P model betters the estimate of terrestrial gross primary productivity - Zhenyu Zhang; Weimin Ju; Xiaoyu Li; Xianfu Cheng; Yanlian Zhou; Shuhao Xu; Chengyu Liu; Jing Li (Agricultural and Forest Meteorology, 2024)

Genotype diversity enhances invasion resistance of native plants via soil biotic feedbacks - Cai Cheng; Zekang Liu; Qun Zhang; Xing Tian; Ruiting Ju; Bo Li; Mark van Kleunen; Jonathan M. Chase; Jihua Wu (Ecology Letters, 2024)
Although native species diversity is frequently reported to enhance invasion resistance, within‐species diversity of native plants can also moderate invasions. While the positive diversity–invasion resistance relationship is often attributed to competition, indirect effects mediated through plant–soil feedbacks can also influence the relationship. We manipulated the genotypic diversity of an endemic species, Scirpus mariqueter , and evaluated the effects of abiotic versus biotic feedbacks on the performance of a global invader, Spartina alterniflora . We found that invader performance on live soils decreased non‐additively with genotypic diversity of the native plant that trained the soils, but this reversed when soils were sterilized to eliminate feedbacks through soil biota. The influence of soil biota on the feedback was primarily associated with increased levels of microbial biomass and fungal diversity in soils trained by multiple‐genotype populations. Our findings highlight the importance of plant–soil feedbacks mediating the positive relationship between genotypic diversity and invasion resistance.

Seismic response of tripod suction bucket foundation for offshore wind turbine in sands - Xinglei Cheng; Yang Li; Kun Mu; M. Hesham El Naggar; Yadong Zhou; Piguang Wang; Xiaohan Sun; Ju Liu (Soil Dynamics and Earthquake Engineering, 2024)

Insights into the effect of hydrochar-derived dissolved organic matter on the sorption of diethyl phthalate onto soil: A pilot mechanism study - Hu Cheng; Yue Zhou; Jingzi Beiyuan; Xiaona Li; Ju Min; Lianghu Su; Longjiang Zhang; Rongting Ji; Jianming Xue (Science of The Total Environment, 2024)

Assessing the impact of government-led green supply chain demonstration on firms' financial distress: The role of environmental information disclosure quality and supply chain concentration - Yingjie Ju; Hanping Hou; Ye Cheng; Yu Feng (Journal of Cleaner Production, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Plugging effects by GPM based two-phase flow in gas drainage fracture: A simulation study - Jianwei Cheng; Dezhi Ran; Yiwen Ju; Qiang Fu; Wang Luo (International Journal of Rock Mechanics and Mining Sciences, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Hydrogen peroxide as a mitigation against Microcystis sp. bloom - Pok Him Ng; Tzu Hsuan Cheng; Ka Yan Man; Liqing Huang; Ka Po Cheng; Kwok Zu Lim; Chi Ho Chan; Maximilian Ho Yat Kam; Ju Zhang; Ana Rita Pinheiro Marques; Sophie St-Hilaire (Aquaculture, 2023)

Miticidal activity of Photorhabdus luminescens for controlling two spider mites, Tetranychus urticae and Tetranychus kanzawai, in Carica papaya - Tzay-Tien Hsieh; Ju-Chun Chang; Chienyan Hsieh; Jui-Tang Tseng; Show-Jow Lin; Cheng-Ju Yang; Feng-Chia Hsieh; Yu-Shin Nai (BioControl, 2023)

Effect of ozone nanobubbles on the microbial ecology of pond water and safety for jade perch (Scortum barcoo) - Qianjun Huang; Pok Him Ng; Ana Rita Pinheiro Marques; Tzu Hsuan Cheng; Ka Yan Man; Kwok Zu Lim; Brett MacKinnon; Liqing Huang; Ju Zhang; Ladan Jahangiri; William Furtado; F.M. Yasir Hasib; et al. (Aquaculture, 2023)

Microplastics in coral reef sediments underestimated? They may hide in biominerals - Chih-Feng Chen; Yun-Ru Ju; Chiu-Wen Chen; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chongtai Ke; Yu-Rong Cheng; Cheng-Di Dong (Science of The Total Environment, 2023)

Reconstituting Cu0/Cu+ synergy with heterostructured CeO2 enabling energy-efficient bipolar hydrogen generation - Xin Zhang; Jing Yu; Hao-Jie Shen; Lu Zhang; Gai-Xiu Yang; Xiao-Cheng Zhou; Jiu-Ju Feng; Ai-Jun Wang (Chemical Engineering Journal, 2023)

In situ generation of highly localized chlorine by laser-induced graphene electrodes during electrochemical disinfection - Ju Zhang; Le Cheng; Liqing Huang; Pok Him Ng; Qianjun Huang; Ana Rita Marques; Brett MacKinnon; Libei Huang; Yefeng Yang; Ruquan Ye; Sophie St-Hilaire (Chemosphere, 2023)

Detoxification of typical nitrogenous heterocyclic compound from pharmaceutical wastewater by mixed microbial consortia - Hongyu Jin; Zimeng Nie; Hongyu Niu; Ju Tan; Shuie Huang; Binghua Yan; Bozhi Cheng; Haijun Yang (Chemosphere, 2023)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Partially miscible droplet microfluidics to enhance interfacial adsorption of hydrophilic nanoparticles for colloidosome synthesis - Wei-Yi Chu; Yi-Ru Chiou; Ren-Hao Luo; Tzu-Heng Chen; Cheng-Ju Yu; Yi-Ju Chou; Huan-Tsung Chang; Chien-Fu Chen (Chemical Engineering Journal, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Analysis of Remote Sensing Monitoring of Atmospheric Ozone in Japan from 2010 to 2021 - Shengtong Lei; Tianzhen Ju; Bingnan Li; Xuhui Xia; Cheng Huang; Jiaming Zhang; Chunxue Li (Water, Air, & Soil Pollution, 2023)

Effect of muscle activation on dynamic responses of neck of pilot during emergency ejection: a finite element study - Tian-Cheng Li; Chun-Jie Liu; Song-Yang Liu; Xin Wang; Jing-Jing Feng; Ju-Tao Wang; Cheng-Fei Du (Medical & Biological Engineering & Computing, 2023)

PPARɑ Ligand Caudatin Improves Cognitive Functions and Mitigates Alzheimer’s Disease Defects By Inducing Autophagy in Mice Models - Senthilkumar Krishnamoorthi; Ashok Iyaswamy; Sravan Gopalkrishnashetty Sreenivasmurthy; Abhimanyu Thakur; Karthick Vasudevan; Gaurav Kumar; Xin-Jie Guan; Kejia Lu; Isha Gaurav; Cheng-Fu Su; Zhou Zhu; Jia Liu; et al. (Journal of Neuroimmune Pharmacology, 2023)

Personal exposure to aldehydes and potential health risks among schoolchildren in the city - Yu-Chuan Yen; Chun-Hung Ku; Tsung-Chieh Yao; Hui-Ju Tsai; Chiung-Yu Peng; Yu-Cheng Chen (Environmental Science and Pollution Research, 2023)

Comprehensive assessment of metals and organic pollutants in pelagic fishing port sediments - Chih-Feng Chen; Shu-Hui Lee; Yun-Ru Ju; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Seasonal distribution of microplastics in the surface waters of the Yellow Sea, China - Weiwei Zhang; Shoufeng Zhang; Ling Qu; Maowei Ju; Cheng Huo; Juying Wang (Marine Pollution Bulletin, 2023)

Analysis on the Influencing Factors and Future Trend of HCHO Pollution in Brazil - Cheng Huang; Tianzhen Ju; Bingnan Li; Jinyang Wang; Jiaming Zhang; Shengtong Lei; Chunxue Li (Water, Air, & Soil Pollution, 2023)

Characteristics and comparisons of the aerobic and anaerobic denitrification of a Klebsiella oxytoca strain: Performance, electron transfer pathway, and mechanism - Cheng-jia Ju; Shareen Niyazi; Wen-yin Cao; Quan Wang; Rong-ping Chen; Lei Yu (Journal of Environmental Management, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

A novel pollution index to assess the metal bioavailability and ecological risks in sediments - Chih-Feng Chen; Yee Cheng Lim; Yun-Ru Ju; Frank Paolo Jay B. Albarico; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

The role of anthraquinone-2-sulfonate on intra/extracellular electron transfer of anaerobic nitrate reduction - Lei Yu; Cheng-jia Ju; Kai-yan Jing; Zi-yang Wang; Shareen Niyazi; Quan Wang (Journal of Environmental Management, 2023)

Combustion simulations of AlH3 and ethanol nanofluid by ReaxFF - Yu-Xiao Cheng; Feng-Qi Zhao; Si-Yu Xu; Xue-Hai Ju; Ying Zhao (Fuel, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Interpenetrating network expansion sponge based on chitosan and plasma for ultrafast hemostasis of arterial bleeding wounds - Yuting Shi; Wenwen Yu; Xiaoqin Liang; Ju Cheng; Yufei Cao; Mingsheng Liu; Yu Fang; Zheng Yang; Hongbin Liu; Hua Wei; Guanghui Zhao (Carbohydrate Polymers, 2023)

Single-plant broccoli growth monitoring using deep learning with UAV imagery - Cheng-Ju Lee; Ming-Der Yang; Hsin-Hung Tseng; Yu-Chun Hsu; Yu Sung; Wei-Ling Chen (Computers and Electronics in Agriculture, 2023)

Protective function and mechanisms of soybean peptides on aluminum maltolate induced brain and liver toxicity on C57BL/6 mice - Yaojun Ju; Dingdong Bu; Bingye Li; Dai Cheng (Food Bioscience, 2023)

A Fully Coupled Thermo-Hydro-Mechanical-Chemical Model for Methane Hydrate Bearing Sediments Considering the Effect of Ice - Fanbao Cheng; Xiang Sun; Peng Wu; Zhixiang Chen; Tao Yu; Weiguo Liu; Xin Ju; Yanghui Li (Journal of Marine Science and Engineering, 2023)
The ice generation is one of the challenges facing the methane hydrate depressurization, which, however, has not been fully addressed by existing numerical models for hydrate-bearing sediments (HBS). In this study, we develop a high-fidelity, fully coupled thermo-hydro-mechanical-chemical numerical model that incorporates the effect of ice. The model, developed using COMSOL, takes into account water–ice phase change, thermally induced cryogenic suction and constitutive relation in HBS. It is verified well against the temperature, pressure and cumulative gas production of Masuda’s experiment. The model is then employed to investigate multiphysical responses and gas/water production when ice generation is induced by setting a low outlet pressure. The results reveal that ice forms near the outlet boundary of the specimen center, leading to a reduction in intrinsic permeability and fluid velocity and an increase in the bulk modulus of ice-HBS. This enhanced bulk modulus results in higher porosity under axial load. Although the exothermic effect of ice generation promotes the hydrate dissociation, the effect on cumulative gas production is negligible after the ice melts. A negative correlation between ice saturation and water production rate is observed, indicating that a higher gas–water ratio can be achieved by adjusting the ice duration during hydrate production. The developed coupled model proves to be crucial for understanding the effect of ice on hydrate exploitation.

Terpenoids with anti-influenza activity from the leaves of Euphorbia leucocephala - Hsiao-Ting Chen; Chi-Wen Chuang; Ju-Chien Cheng; Yung-Ju Yeh; Tsung-Hsien Chang; Yu-Ting Shi; Chih-Hua Chao (Natural Product Research, 2023)

The identification of soy sauce adulterated with bean species and the origin using headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry - Wei-Chen Wang; Yi-Feng Zheng; Shau-Chun Wang; Cheng-Yu Kuo; Han-Ju Chien; Xiang-Gui Hong; Yu-ming Hsu; Chien-Chen Lai (Food Chemistry, 2023)

Establishment of a CaCC-based Cell Model and Method for High-throughput Screening of M3 Receptor Drugs - Xueying Liu; Xiaohong Ju; Qiyuan Hong; Ximin Wang; Mingda Wu; Wenzhu Xing; Meng Xu; Cheng Hu; Feng Hao (Cell Biochemistry and Biophysics, 2023)

Improving the capability of D-InSAR combined with offset-tracking for monitoring glacier velocity - Xiaoman Feng; Zhuoqi Chen; Gang Li; Qi Ju; Zhibing Yang; Xiao Cheng (Remote Sensing of Environment, 2023)

Effect of Moisture on Time-Varying Diffusion Properties of Methane in Low-Rank Coal - Jingyu Jiang; Huizhen Peng; Yuanping Cheng; Liang Wang; Chenghao Wang; Sen Ju (Transport in Porous Media, 2023)

Observational analyses of a penetrating sea-breeze front in the Beijing-Tianjin-Hebei urban agglomeration - Ju Li; Yubing Pan; Qingchun Li; Donald H. Lenschow; Mingyu Zhou; Xian Xiao; Yaoting Wang; Zhigang Cheng (Urban Climate, 2023)

Unique responses of Cu-SSZ-13 toward phosphorus: Al atoms on zeolite framework versus varied Cu species - Jingang Wang; Jianbo Zhang; Cheng Xing; Taosheng Jin; Jinpeng Liu; Meiting Ju; Xuejiao Tang (Chemical Engineering Journal, 2023)

Quantitative lateral flow immunoassay for rapid detection of procollagen type I N-terminal propeptide in the monitoring of osteoporosis treatment - Chung-An Chen; Ping-Yeh Chiu; Tse-Hao Huang; Natalie Yi-Ju Ho; Fu-Cheng Kao; Tsung-Ting Tsai (Analytica Chimica Acta, 2023)

Development of the dried blood spot preparation protocol for comprehensive evaluation of the hematocrit effect - Chih-Ning Cheng; Yu-Fong Peng; Ju-Yu Chen; Guan-Yuan Chen; Te-I Weng; Ching-Hua Kuo (Analytica Chimica Acta, 2023)

CRIF1 promotes the progression of non-small-cell lung cancer by SIRT3- mediated deacetylation of PYCR1 - Qi Wang; Zhuolin Xie; Chang Li; Chun Xu; Cheng Ding; Sheng Ju; Jun Chen; Zihan Cui; Chen Chen; Biao Gu; Tengteng Wei; Jun Zhao (Journal of Molecular Histology, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Synergistic interactions of plant essential oils with antimicrobial agents: a new antimicrobial therapy - Jian Ju; Yunfei Xie; Hang Yu; Yahui Guo; Yuliang Cheng; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

The effects of immersive garden experience on the health care to elderly residents with mild-to-moderate cognitive impairment living in nursing homes after the COVID-19 pandemic - Chung-Heng Hsieh; Cheng-Min Chen; Ju-Yuan Yang; Yen-Ju Lin; Man-Li Liao; Ke-Hsin Chueh (Landscape and Ecological Engineering, 2022)

Quantitative Relationships between the Tidal Current Limit, Tidal Level Limit and River Discharge in the Changjiang River Estuary - Chengcheng Hou; Jianrong Zhu; Ju Huang; Xinyue Cheng (Journal of Marine Science and Engineering, 2021)
Estuaries are areas where runoff and tide interact. Tidal waves propagate upstream from river mouths and produce tidal currents and tidal level variations along rivers. Based on the hydrological frequency analysis of river discharge in the dry season and flood season at the Datong hydrological station over the past 70 years, a three-dimensional estuary numerical model was used to produce the quantitative relationships between the tidal current limit, tidal level limit and river discharge in the Changjiang River estuary. The positions of tidal current limit and tidal level limit depend not only on river discharge but also on river topography. When river discharge varies from a hydrological frequency of 95% to 5%, the relationship between the tidal current limit and river discharge is y=2×10−13x3+3 × 10−8x2− 0.0074x+359.35 in the flood season, with a variation range of 90 km, and y=−4×10−10x3−1 × 10−5x2−0.1937x − 1232.9 in the dry season, with a variation range of 200 km. The relationship between the tidal level limit and river discharge is y=6×10−8x2−0.0096x+775.94 in the flood season, with a variation range of 127 km, and y=0.3428x2−17.9x+777.55 in the dry season, with a variation range of 83 km, which is located far upstream of the Datong hydrological station.

TLR2 Potentiates SR-Marco-Mediated Neuroinflammation by Interacting with the SRCR Domain - Lu Wang; Han-Yu Yang; Cai-Xia Zang; Jun-Mei Shang; Hui Liu; Zi-Hong Zhang; Fang-Yu Yuan; Cheng Ju; Fang-Yuan Li; Xiu-Qi Bao; Dan Zhang (Molecular Neurobiology, 2021)

Divergence in the Aquilegia ecalcarata complex is correlated with geography and climate oscillations: Evidence from plastid genome data - Cheng Xue; Fang‐Dong Geng; Jiao‐Jie Li; Dan‐Qing Zhang; Fei Gao; Lei Huang; Xiao‐Hui Zhang; Ju‐Qing Kang; Jian‐Qiang Zhang; Yi Ren (Molecular Ecology, 2021)
Quaternary climate oscillations and geographical heterogeneity play important roles in determining species and genetic diversity distribution patterns, but how these factors affect the migration and differentiation of East Asian plants species at the population level remains poorly understood. The Aquilegia ecalcarata complex, a group that originated in the Late Tertiary and is widely distributed throughout East Asia, displays high genetic variation that is suitable for studying elaborate phylogeographic patterns and demographic history related to the impact of Quaternary climate and geography. We used plastid genome data from 322 individuals in 60 populations of the A . ecalcarata complex to thoroughly explore the impact of Quaternary climate oscillations and geography on the phylogeographic patterns and demographic history of the A . ecalcarata complex through a series of phylogenetic, divergence time estimation, and demographic history analyses. The dry, cold climate and frequent climate oscillations that occurred during the early Pleistocene and the Mid‐Pleistocene transition led to the differentiation of the A . ecalcarata complex, which was isolated in various areas. Geographically, the A . ecalcarata complex can be divided into Eastern and Western Clades and five subclades, which conform to the divergence of the East Asian flora. Our results clearly show the impact of Quaternary climate and geography on evolutionary history at the population level. These findings promote the understanding of the relationship between plant genetic differentiation and climate and geographical factors of East Asia at the population level.

Resveratrol Mitigates Cerebral Ischemic Injury by Altering Levels of Trace Elements, Toxic Metal, Lipid Peroxidation, and Antioxidant Activity - Ju-Hai Ro; Chien-Chi Liu; Ming-Cheng Lin (Biological Trace Element Research, 2021)

Evolutionary Changes in Pathways and Networks of Genes Expressed in the Brains of Humans and Macaques - Yuequn Ma; Changying Cao; Mengwen Zhao; Xinhua Liu; Feng Cheng; Ju Wang (Journal of Molecular Neuroscience, 2021)

Molecular cloning and sequence analysis of a mitogen-activated protein kinase gene in the Antarctic yeast Rhodotorula mucilaginosa AN5 - Cuijuan Shi; Hong Zhang; Kai Yu; Yingying Wang; Jie Jiang; Yun Ju; Chuanzhou Zhang; Ziyi Cheng; Guangfeng Kan (Molecular Biology Reports, 2021)

Patient Confidential Information Transmission Using the Integration of PSO-Based Biomedical Signal Steganography and Threshold-Based Compression - Shih-Ying Chen; Shan-Ju Lin; Ming-Cheng Tsai; Ming-Dar Tsai; Yih-Jing Tang; Shuo-Tsung Chen; Li-Hsiang Wang (Journal of Medical and Biological Engineering, 2021)

The developmental regulator PatD modulates assembly of the cell‐division protein FtsZ in the cyanobacterium Anabaena sp. PCC 7120 - Li Wang; Tian‐Cai Niu; Ana Valladares; Gui‐Ming Lin; Ju‐Yuan Zhang; Antonia Herrero; Wen‐Li Chen; Cheng‐Cai Zhang (Environmental Microbiology, 2021)
Summary FtsZ is a tubulin‐like GTPase that polymerizes to initiate the process of cell division in bacteria. Heterocysts are terminally differentiated cells of filamentous cyanobacteria that have lost the capacity for cell division and in which the ftsZ gene is downregulated. However, mechanisms of FtsZ regulation during heterocyst differentiation have been scarcely investigated. The patD gene is NtcA dependent and involved in the optimization of heterocyst frequency in Anabaena sp. PCC 7120. Here, we report that the inactivation of patD caused the formation of multiple FtsZ‐rings in vegetative cells, cell enlargement, and the retention of peptidoglycan synthesis activity in heterocysts, whereas its ectopic expression resulted in aberrant FtsZ polymerization and cell division. PatD interacted with FtsZ, increased FtsZ precipitation in sedimentation assays, and promoted the formation of thick straight FtsZ bundles that differ from the toroidal aggregates formed by FtsZ alone. These results suggest that in the differentiating heterocysts, PatD interferes with the assembly of FtsZ. We propose that in Anabaena FtsZ is a bifunctional protein involved in both vegetative cell division and regulation of heterocyst differentiation. In the differentiating cells PatD‐FtsZ interactions appear to set an FtsZ activity that is insufficient for cell division but optimal to foster differentiation.

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Assessing the Influence of Aerosol on Radiation and Its Roles in Planetary Boundary Layer Development - Zhigang Cheng; Yubing Pan; Ju Li; Xingcan Jia; Xinyu Zhang; Pengkun Ma; Qianqian Wang; Junxia Dou; Jingjiang Zhang; Jiannong Quan (Journal of Meteorological Research, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Knockdown of Amphiregulin Triggers Doxorubicin-Induced Autophagic and Apoptotic Death by Regulating Endoplasmic Reticulum Stress in Glioblastoma Cells - I-Neng Lee; Jen-Tsung Yang; Ming-Ju Hsieh; Cheng Huang; Hsiu-Chen Huang; Yu-Ju Ku; Yu-Ping Wu; Kuan-Chieh Huang; Jui-Chieh Chen (Journal of Molecular Neuroscience, 2020)

Application of starch microcapsules containing essential oil in food preservation - Jian Ju; Yunfei Xie; Yahui Guo; Yuliang Cheng; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2020)

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Luminescent Coordination Polymer for Picric Acid Detection and Treatment on Spinal Cord Injury Model Via Upregulating the trka Expression - Cheng-Hu Wang; Bin Sheng; Zhi Zhang; Ming Deng; Jin-Ju Xue; Yong-Gang Ma (Journal of Fluorescence, 2020)

The protective effects of Mogroside V and its metabolite 11-oxo-mogrol of intestinal microbiota against MK801-induced neuronal damages - Peijun Ju; Wenhua Ding; Jianhua Chen; Ying Cheng; Beibei Yang; Lanting Huang; Qiong Zhou; Cuizhen Zhu; Xiaobo Li; Mengyue Wang; Jinghong Chen (Psychopharmacology, 2020)

Optimization of the OCO-2 Cloud Screening Algorithm and Evaluation against MODIS and TCCON Measurements over Land Surfaces in Europe and Japan - Sijie Chen; Shuaibo Wang; Lin Su; Changzhe Dong; Ju Ke; Zhuofan Zheng; Chonghui Cheng; Bowen Tong; Dong Liu (Advances in Atmospheric Sciences, 2020)

Effects of telomere length on leukemogenesis - Shihui Ma; Guohuan Sun; Shangda Yang; Zhenyu Ju; Tao Cheng; Hui Cheng (Science China Life Sciences, 2020)

LPS impairs steroidogenesis and ROS metabolism and induces PPAR transcriptional activity to disturb estrogen/androgen receptor expression in testicular cells - Gang Wang; Songtao Cheng; Shanshan Zhang; Yuan Zhu; Yu Xiao; Lingao Ju (Molecular Biology Reports, 2020)

Overexpression LINC01082 suppresses the proliferation, migration and invasion of colon cancer - Wei Xiong; Jiyong Qin; Xinyi Cai; Wei Xiong; Qiuyan Liu; Cheng Li; Yunhe Ju; Qiaoli Wang; Yunfeng Li; Yi Yang (Molecular and Cellular Biochemistry, 2019)

The inhibitory effect of plant essential oils on foodborne pathogenic bacteria in food - Jian Ju; Yunfei Xie; Yahui Guo; Yuliang Cheng; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2019)

An integrative assessment to determine the sediment toxicity of Kaohsiung Harbor in Taiwan: combining chemical analysis and cytotoxicity assay - Yun-Ru Ju; Chih-Feng Chen; Chiu-Wen Chen; Mei-Ling Tsai; Jia-Ching Wu; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Effect of metals on zooplankton abundance and distribution in the coast of southwestern Taiwan - Yun-Ru Ju; Wen-Tseng Lo; Chih-Feng Chen; Chiu-Wen Chen; Zhi-Ling Huang; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Application of edible coating with essential oil in food preservation - Jian Ju; Yunfei Xie; Yahui Guo; Yuliang Cheng; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2019)

Synthesis of oleanolic acid/ursolic acid/glycyrrhetinic acid-hydrogen sulfide donor hybrids and their antitumor activity - Li-xin Sheng; Jia-yan Huang; Chun-mei Liu; Ju-zheng Zhang; Ke-guang Cheng (Medicinal Chemistry Research, 2019)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

Modelling spatial variation in the treatment costs of non-point source pollution in mountainous regions of southwest China - Ju Liu; Bin Fu; Cheng-hu Zhang; Yu-kuan Wang (Journal of Mountain Science, 2019)

Spatial distribution and ecological risk assessment of sediment metals in a highly industrialized coastal zone southwestern Taiwan - Chiu-Wen Chen; Yee Cheng Lim; Chih-Feng Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2019)

Health risk of metal exposure via inhalation of cigarette sidestream smoke particulate matter - Li-Chuan Cheng; Chun-Ju Lin; Huei-Ju Liu; Lih-Ann Li (Environmental Science and Pollution Research, 2019)

Neonatal Dexamethasone Treatment Suppresses Hippocampal Estrogen Receptor α Expression in Adolescent Female Rats - Hui-Fang Chiu; Michael W. Y. Chan; Chiung-Yin Cheng; Jian-Liang Chou; Jora Meng-Ju Lin; Yi-Ling Yang; Kwok-Tung Lu (Molecular Neurobiology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Mild Hypothermia Prevents NO-Induced Cytotoxicity in Human Neuroblastoma Cells Via Induction of COX-2 - Bing-Bing Lei; Fei Ju; Qi-Ran Fu; Xin Yuan; Wen-Xin Song; Guo-Qin Ji; Kai-Yu Lei; Lei Wang; Bin-Feng Cheng; Mian Wang; Hai-Jie Yang (Journal of Molecular Neuroscience, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

The relative importance of space compared to topography increases from rare to common tree species across latitude - Yue‐Hua Hu; Daniel J. Johnson; Xiang‐Cheng Mi; Xu‐Gao Wang; Wan‐Hui Ye; Yi‐De Li; Ju‐Yu Lian; Min Cao (Journal of Biogeography, 2018)
Aim Understanding how spatial distributions of rare and common species are associated with environmental and spatial processes is essential to understanding community assembly. We addressed the following questions: (a) does the relative importance of space and topography vary from rare to common tree species? (b) Are the contributions of topography and space equal? (c) Are the variances explained by topography or space correlated with elevational ranges (ER) at the local scale? (d) Does cell‐size influence those postulated associations? Location China and the Americas. Major taxa studied Tree species. Methods We partitioned the variation in species richness and composition of rare and common tree species by topography and space across a range of extents and grain sizes in eight communities. We calculated contribution ratio ( CR ) between space and topography to quantify their relative importance. We employed Kendall's rank correlation to determine the relation between CR and commonness. Mixed effect models were used to identify the influence of cell‐size on the results. Results The majority of CR values were positively related to increasing commonness, especially for composition. The explained variances by space were always higher than that by topography regardless of commonness. At local scale, variances explained by space or topography were not correlated with ER. Main conclusions Our results indicate that the relative importance of space compared to topography increases from rare to common species across forests. We suggest that future studies of community assembly need to account for both space and topography to adequately describe differences in rare and common species assembly mechanisms at range of spatial extents and grain sizes.

Late Pleistocene aeolian activity in Haitan Island, Southeast China: Insights from optically stimulated luminescence dating of coastal dunes on marine terraces - Jian-hui Jin; Zhi-zhong Li; Yan Cheng; Xiao-lin Xu; Zhi-xing Li; Xiao-ju Liu (Journal of Mountain Science, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

Immunogenicity of adenovirus and DNA vaccines co-expressing P39 and lumazine synthase proteins of Brucella abortus in BALB/c mice - Guo-Zhen Lin; Ju-Tian Yang; Suo-Cheng Wei; Shi-En Chen; Sheng-Dong Huo; Zhong-Ren Ma (Tropical Animal Health and Production, 2018)

A new aromatic glycoside and its anti-proliferative activities from the leaves of Bergenia purpurascens - Shan-Shan Zhang; Zhi-Xin Liao; Ri-Zhen Huang; Cheng-Cheng Gong; Lan-Ju Ji; Hong-Fa Sun (Natural Product Research, 2018)

Sediment control function of river notches - Chia-Hsing Lin; Cheng-Ju Liu; Shih-Hsun Lin; Chjeng-Lun Shieh (Journal of Mountain Science, 2018)

Facultative production of multiple-egg clutches in a quasi-gregarious parasitoid: fitness gains for offspring at low developmental temperature - Peng-Cheng Liu; Ju Luo; Shuo Tian; Shao-Ying Wen; Jian-Rong Wei; De-Jun Hao (Behavioral Ecology and Sociobiology, 2018)

Prevalence of NS5B resistance-associated variants in treatment-naïve Asian patients with chronic hepatitis C - Song Yang; Huichun Xing; Shenghu Feng; Wei Ju; Shunai Liu; Xiaomei Wang; Weini Ou; Jun Cheng; Calvin Q. Pan (Archives of Virology, 2018)

Phytotoxic, antibacterial, and antioxidant activities of mycotoxins and other metabolites from Trichoderma sp. - Ju-cheng Zhang; Guang-Yi Chen; Xiao-Zhan Li; Ming Hu; Bang-Yan Wang; Bao-Hui Ruan; Hao Zhou; Li-Xing Zhao; Jun Zhou; Zhong-Tao Ding; Ya-Bin Yang (Natural Product Research, 2017)

Isolation, molecular characterization and an artificial infection model for a variant porcine epidemic diarrhea virus strain from Jiangsu Province, China - Hewei Zhang; Mingqi Xia; Decai Ju; Bai Wu; Chen Ning; Ni Song; Teng Feng; Feng Chen; Xin Wang; Ying Wu; Wei Wang; Shipeng Cheng; et al. (Archives of Virology, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Identification of 3-MCPD esters to verify the adulteration of extra virgin olive oil - Wei-Ching Hung; Guan-Jhih Peng; Wen-Ju Tsai; Mei-Hua Chang; Chia-Ding Liao; Su-Hsiang Tseng; Ya-Min Kao; Der-Yuan Wang; Hwei-Fang Cheng (Food Additives & Contaminants Part B-Surveillance, 2017)

Evaluation on subcellular partitioning and biodynamics of pulse copper toxicity in tilapia reveals impacts of a major environmental disturbance - Yun-Ru Ju; Ying-Fei Yang; Jeng-Wei Tsai; Yi-Hsien Cheng; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

ApoA-I/SR-BI modulates S1P/S1PR2-mediated inflammation through the PI3K/Akt signaling pathway in HUVECs - Kun Ren; Yan-Ju Lu; Zhong-Cheng Mo; Xing -Liu; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Li Li; Qing-Hai Zhang; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2017)

Antipsychotic use is a risk factor for hyponatremia in patients with schizophrenia: a 15-year follow-up study - Hang-Ju Yang; Wan-Ju Cheng (Psychopharmacology, 2017)

Theoretical investigation of congener-specific soil sorption of polychlorinated biphenyls by DFT computation and potent QSAR analyses - Mengrong Zhu; Chenggang Gu; Yinwen Cheng; Xuehai Ju; Yongrong Bian; Xinglun Yang; Yang Song; Mao Ye; Fang Wang; Xin Jiang (Journal of Soils and Sediments, 2017)

Thrombospondin-4 Promotes Neuronal Differentiation of NG2 Cells via the ERK/MAPK Pathway - Hai Jie Yang; Shuang Ping Ma; Fei Ju; Ya Ping Zhang; Zhi Chao Li; Bin Bin Zhang; Jun Jiang Lian; Lei Wang; Bin Feng Cheng; Mian Wang; Zhi Wei Feng (Journal of Molecular Neuroscience, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Optimum dredging time for inhibition and prevention of algae-induced black blooms in Lake Taihu, China - Chao Chen; Ji-Cheng Zhong; Ju-Hua Yu; Qiu-Shi Shen; Cheng-Xin Fan; Fan-Xiang Kong (Environmental Science and Pollution Research, 2016)

DTC-GO as Effective Adsorbent for the Removal of Cu2+ and Cd2+ from Aqueous Solution - Li-Juan Guo; Cheng-Gang Niu; Xiao-Yu Wang; Xiao-Ju Wen; Guang-Ming Zeng (Water, Air, & Soil Pollution, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Vertical profile, source apportionment, and toxicity of PAHs in sediment cores of a wharf near the coal-based steel refining industrial zone in Kaohsiung, Taiwan - Chih-Feng Chen; Chiu-Wen Chen; Yun-Ru Ju; Cheng-Di Dong (Environmental Science and Pollution Research, 2016)

Seasonal difference of human adenoviruses in a subtropical river basin based on 1-year monthly survey - Chi-Wei Tao; Bing-Mu Hsu; Po-Min Kao; Wen-Chien Huang; Tsui-Kang Hsu; Ying-Ning Ho; Yen-Ju Lu; Cheng-Wei Fan (Environmental Science and Pollution Research, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Mean Structure and Fluctuations of the Kuroshio East of Taiwan from In Situ and Remote Observations - Ying Jang Yang; Sen Jan; Ming-Hueh Chang; Joe Wang; Vegan Mensah; Tien-Hsia Kuo; Cheng-ju Tsai; Chung Yaung Lee; Magdalena Andres; Luca Centurioni; Yu-Heng Tseng; Wen-Der LIang; et al. (Oceanography, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Analysis of ovary DNA methylation during delayed fertilization in hazel using the methylation-sensitive amplification technique - Yunqing Cheng; Ju Wang; Jianfeng Liu; Yixin Zhao; Wanting Geng; Huidi Zhang (Acta Physiologiae Plantarum, 2015)

Thalamic resting-state functional connectivity: disruption in patients with type 2 diabetes - Yu-Chen Chen; Wenqing Xia; Cheng Qian; Jie Ding; Shenghong Ju; Gao-Jun Teng (Metabolic Brain Disease, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Robot-Assisted Passive Exercise for Ankle Hypertonia in Individuals with Chronic Spinal Cord Injury - Chia-Ying Fang; Miao-Ju Hsu; Chih-Chung Chen; Hsin-Yi Kathy Cheng; Ching-Chieh Chou; Ya-Ju Chang (Journal of Medical and Biological Engineering, 2015)

Nocardia rhizosphaerae sp. nov., a novel actinomycete isolated from the coastal rhizosphere of Artemisia Linn., China - Yu Wang; Wei Liu; Wei-Wei Feng; Xiao-Qi Zhou; Juan-Luan Bai; Bo Yuan; Xiu-Yun Ju; Cheng-Liang Cao; Ying Huang; Ji-Hong Jiang; Ai-Jun Lv; Sheng Qin (Antonie van Leeuwenhoek, 2015)

Tissue lipid metabolism and hepatic metabolomic profiling in response to supplementation of fermented cottonseed meal in the diets of broiler chickens - Cun-xi Nie; Wen-ju Zhang; Yong-qiang Wang; Yan-feng Liu; Wen-xia Ge; Jian-cheng Liu (Journal of Zhejiang University-SCIENCE B, 2015)

The Effect of Dextransucrase Gene Inactivation on Mannitol Production by Leuconostoc mesenteroides - Zhou Zhang; Wen-Yu Cheng; Xiao-Yan Ju; Hong-Xing Jin (Indian Journal of Microbiology, 2015)

Integrated risk assessment method of waterlog disaster in Huaihe River Basin of China - Ju-Liang Jin; Juan Fu; Yi-Ming Wei; Shang-Ming Jiang; Yu-Liang Zhou; Li Liu; You-Zhen Wang; Cheng-Guo Wu (Natural Hazards, 2015)

Comprehensive evaluation of ice disaster risk of the Ningxia–Inner Mongolia Reach in the upper Yellow River - Cheng-Guo Wu; Yi-Ming Wei; Ju-Liang Jin; Qiang Huang; Yu-Liang Zhou; Li Liu (Natural Hazards, 2015)

Changes of rural to urban areas in hydrograph characteristics on watershed divisions - Jet-chau Wen; Yen-jen Lee; Shin-jen Cheng; Ju-huang Lee (Natural Hazards, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Combined effects of the BDNF rs6265 (Val66Met) polymorphism and environment risk factors on psoriasis vulgaris - Cheng Quan; Kun-Ju Zhu; Chi Zhang; Zhong Liu; Huan Liu; Cheng-Yao Zhu; Ke-Shen Li; Yi-Ming Fan; Jie Zheng (Molecular Biology Reports, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

Cytoprotective effects of 6′-O-galloylpaeoniflorin against ultraviolet B radiation-induced cell damage in human keratinocytes - Cheng Wen Yao; Mei Jing Piao; Ki Cheon Kim; Jian Zheng; Ji Won Cha; Chang Lim Hyun; Sun Jin Boo; Soo Young Na; Suk Ju Cho; Jin Won Hyun (In Vitro Cellular & Developmental Biology - Animal, 2014)

Rickettsia raoultii, the predominant Rickettsia found in Dermacentor silvarum ticks in China–Russia border areas - Jing Wen; Dan Jiao; Jian-hua Wang; De-hai Yao; Zhi-xiang Liu; Gang Zhao; Wen-dong Ju; Cheng Cheng; Yi-jing Li; Yi Sun (Experimental and Applied Acarology, 2014)

Effect of 7, 8-dihydroxyflavone on the up-regulation of Nrf2-mediated heme oxygenase-1 expression in hamster lung fibroblasts - Min Ju Ryu; Kyoung Ah Kang; Mei Jing Piao; Ki Cheon Kim; Jian Zheng; Cheng Wen Yao; Ji Won Cha; Chang Lim Hyun; Ha Sook Chung; Jong Cook Park; Suk Ju Cho; Jin Won Hyun (In Vitro Cellular & Developmental Biology - Animal, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Temporal characteristics of black carbon concentrations and its potential emission sources in a southern Taiwan industrial urban area - Yu-Hsiang Cheng; Chi-Chi Lin; Jyh-Jian Liu; Cheng-Ju Hsieh (Environmental Science and Pollution Research, 2014)

Neuroglobin Promotes Neurite Outgrowth via Differential Binding to PTEN and Akt - Li Li; Qian Rong Liu; Xin Xin Xiong; Ju Mei Liu; Xiao Jing Lai; Chun Cheng; Feng Pan; Yong Chen; Shang Bin Yu; Albert Cheung Hoi Yu; Xiao Qian Chen (Molecular Neurobiology, 2014)

miR-154 inhibits EMT by targeting HMGA2 in prostate cancer cells - Chen Zhu; Jie Li; Gong Cheng; Hai Zhou; Liangjun Tao; Hongzhou Cai; Pu Li; Qiang Cao; Xiaobing Ju; Xiaoxin Meng; Meilin Wang; Zhengdong Zhang; et al. (Molecular and Cellular Biochemistry, 2013)

Tail loss compromises immunity in the many-lined skink, Eutropis multifasciata - Chi-Chien Kuo; Chiou-Ju Yao; Te-En Lin; Hsu-Che Liu; Yu-Cheng Hsu; Ming-Kun Hsieh; Wen-San Huang (The Science of Nature, 2013)

Circulating IL-21 levels increase during early simian-human immunodeficiency virus infection in macaques - Chang-cheng Zhao; Jing Xue; Zhe Cong; Xi-qiang Gao; Wei-lun Zhang; Ting Chen; Fang-xin Wu; Jing Xiong; Bin Ju; Aihua Su; Qiang Wei; Chuan Qin (Archives of Virology, 2013)

Association of IL23R polymorphisms with psoriasis and psoriatic arthritis: a meta-analysis - Kun-Ju Zhu; Cheng-Yao Zhu; Ge Shi; Yi-Ming Fan (Inflammation Research, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Assessing the impact of climate change on basin-average annual typhoon rainfalls with consideration of multisite correlation - Yii-Chen Wu; Ju-Chen Hou; Jun-Jih Liou; Yuan-Fong Su; Ke-Sheng Cheng (Paddy and Water Environment, 2012)

The impacts of natural hazards on Taiwan’s tourism industry - Hsien-Tang Tsai; Cheng-Jui Tseng; Shian-Yang Tzeng; Tung-Ju Wu; Jen-der Day (Natural Hazards, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

Decontamination of Bacillus subtilis var. niger spores on selected surfaces by chlorine dioxide gas - Yan-ju Li; Neng Zhu; Hai-quan Jia; Jin-hui Wu; Ying Yi; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2012)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Application of multiplex reverse transcription-ligase detection reaction-polymerase chain reaction (MRLP) mediated universal DNA microarray for detecting potato viruses in field samples - Ping Wang; Yao Guo; Ju-Hui Cheng; Qin-Fang Dong; Xian-Feng Ding; Jiang-Feng Guo; Yong-Hou Jiang (European Journal of Plant Pathology, 2012)

Identifying hydrograph parameters and their relationships to urbanization variables - Shao-Yang Huang; Shin-Jen Cheng; Jet-Chau Wen; Ju-Huang Lee (Hydrological Sciences Journal, 2012)

Effects of Raingauge Distribution on Estimation Accuracy of Areal Rainfall - Chun-dan Cheng; Shin-jen Cheng; Jet-chau Wen; Ju-huang Lee (Water Resources Management, 2012)

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

Cometabolic biotransformation of fenpropathrin by Clostridium species strain ZP3 - Songbai Zhang; Lebin Yin; Yong Liu; Deyong Zhang; Xiangwen Luo; Ju’e Cheng; Feixue Cheng; Jianping Dai (Biodegradation, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Genetic diversity and differentiation of cultivated ginseng (Panax ginseng C. A. Meyer) populations in North-east China revealed by inter-simple sequence repeat (ISSR) markers - Shan Li; Jing Li; Xiao-Ling Yang; Zhou Cheng; Wen-Ju Zhang (Genetic Resources and Crop Evolution, 2011)

Four new xarifiid copepods (Poecilostomatoida) associated with the scleractinian coral Pavona explanulata (Lamarck) from off Taiwan - Yu-Rong Cheng; Ju-shey Ho; Chang-Feng Dai (Systematic Parasitology, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

The computation of a finite-frequency travel time sensitive kernel for P-waves in the AK135 earth model - Feng-Xue Zhang; Qing-Ju Wu; Jia-Tie Pan; Guang-Cheng Zhang; Qiang-Qiang Feng (Applied Geophysics, 2011)

Stochastic simulation of bivariate gamma distribution: a frequency-factor based approach - Ke-Sheng Cheng; Ju-Chen Hou; Jun-Jih Liou; Yii-Chen Wu; Jie-Lun Chiang (Stochastic Environmental Research and Risk Assessment, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Diversity and paleobiogeographic distribution patterns of early and Middle Ordovician graptolites in distinct depositional environments of South China - YuanDong Zhang; Xu Chen; Goldman Dan; Ju Zhang; JunFeng Cheng; YanYan Song (Science China Earth Sciences, 2010)

Genome relationships in the genus Dasypyrum: evidence from molecular phylogenetic analysis and in situ hybridization - Cheng Liu; Guang-Rong Li; Sunish Kumar Sehgal; Ju-Qing Jia; Zu-Jun Yang; Bernd Friebe; Bikram Gill (Plant Systematics and Evolution, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

Characterization of a new dehydration responsive element binding factor in central arctic cowberry - Qing-Ju Wang; Kuan-Yong Xu; Zhao-Guo Tong; San-Hong Wang; Zhi-Hong Gao; Ji-Yu Zhang; Cheng-Wen Zong; Yu-Shan Qiao; Zhen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

A new butanolide and a new secobutanolide from Litsea lii var. nunkao - tahangensis - Ming-Jen Cheng †; Tzu-Ann Wang †; Shiow-Ju Lee; Ih-Sheng Chen (Natural Product Research, 2010)

Effects of Urbanization Factors on Model Parameters - Shin-jen Cheng; Cheng-feng Lee; Ju-huang Lee (Water Resources Management, 2010)

Trigonostemon tuberculatus (Euphorbiaceae), a peculiar new species from Yunnan Province, China - Du Fan; He Ju; Yang Shao-Yong; Cheng Xia; Zhang Da-Cai; Tang Ye-Na (Kew Bulletin, 2010)

Magnesium sulfate enhances exercise performance and manipulates dynamic changes in peripheral glucose utilization - Shiu-Min Cheng; Lin-Lan Yang; Sy-Huah Chen; Mei-Hsiang Hsu; I-Ju Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2010)

Assessing the impact of climate change on annual typhoon rainfall—a stochastic simulation approach - Ke-Sheng Cheng; Ju-Chen Hou; Yii-Chen Wu; Jun-Jih Liou (Paddy and Water Environment, 2009)

Orstomella yaliuensis n. sp., a xarifiid copepod (Crustacea) parasitic in the polyps of hump coral Porites lutea Milne Edwards & Haime off Taiwan - Yu-Rong Cheng; Ju-shey Ho; Chang-Feng Dai (Systematic Parasitology, 2009)

Development of a Whole-organism Model to Screen New Compounds for Sun Protection - Yun-Hsin Wang; Chi-Chung Wen; Zhi-Shiang Yang; Chien-Chung Cheng; Jen-Ning Tsai; Chia-Chen Ku; Hsin-Ju Wu; Yau-Hung Chen (Marine Biotechnology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

The predictive role of E2-EPF ubiquitin carrier protein in esophageal squamous cell carcinoma - Miao-Fen Chen; Kuan-Der Lee; Ming-Shian Lu; Chih-Cheng Chen; Ming-Ju Hsieh; Yun-Hen Liu; Paul-Yang Lin; Wen-Cheng Chen (Journal of Molecular Medicine, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Distinctive osteology of distal flipper bones of tropical bottlenose whales, Indopacetus pacificus , from Taiwan: Mother and calf, calf with polydactyly - Alastair Watson; Tzong‐Fu Kuo; Wei‐Cheng Yang; Chiuo‐Ju Yao; Lien‐Siang Chou (Marine Mammal Science, 2008)

Forecasting flood disasters using an accelerated genetic algorithm: Examples of two case studies for China - Ju-Liang Jin; Jian Cheng; Yi-Ming Wei (Natural Hazards, 2008)

Complete sequence of a subgroup 3.4 strain of classical swine fever virus from Taiwan - Yu-Ju Lin; Maw-Sheng Chien; Ming-Chung Deng; Chin-Cheng Huang (Virus Genes, 2007)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Interleukin-18 gene polymorphism, but not interleukin-2 gene polymorphism, is associated with rheumatoid arthritis - Cheng-Chun Lee; Wei-Yong Lin; Lei Wan; Yuhsin Tsai; Ying-Ju Lin; Chang-Hai Tsai; Chung-Ming Huang; Fuu-Jen Tsai (Immunogenetics, 2007)

Improving freezing tolerance of transgenic tobacco expressing sucrose: sucrose 1-fructosyltransferase gene from Lactuca sativa - Hui-Juan Li; Ai-Fang Yang; Xue-Cheng Zhang; Feng Gao; Ju-Ren Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Model-based ankle joint angle tracing by cuff electrode recordings of peroneal and tibial nerves - Chou-Ching K. Lin; Ming-Shaung Ju; Hang-Shing Cheng (Medical & Biological Engineering & Computing, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Biodegradation of crystal violet by Pseudomonas putida - Chiing-Chang Chen; Hung-Ju Liao; Chiu-Yu Cheng; Chia-Yuen Yen; Ying-Chien Chung (Biotechnology Letters, 2007)

Effect of aristolochic acid on intracellular calcium concentration and its links with apoptosis in renal tubular cells - Yi-Hong Hsin; Chi-Hung Cheng; Jason T. C. Tzen; Ming-Ju Wu; Kuo-Hsiung Shu; Hong-Chen Chen (Apoptosis, 2006)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Odorous swine wastewater treatment by purple non-sulfur bacteria, Rhodopseudomonas palustris, isolated from eutrophicated ponds - Myung Kyum Kim; Kyung-Min Choi; Cheng-Ri Yin; Ki-Young Lee; Wan-Taek Im; Ju Hyoung Lim; Sung-Taik Lee (Biotechnology Letters, 2004)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Genetic diversity of alligator weed in China by RAPD analysis - Cheng-Yuan Xu; Wen-Ju Zhang; Cui-Zhang Fu; Bao-Rong Lu (Biodiversity and Conservation, 2003)

Novel action of lignans isolated from Hernandia nymphaeifolia on Ca2+ signaling in human neutrophils - Yu-Ying Chao; Warren Su; Chung-Ren Jan; Ying-Chin Ko; Jih-Jung Chen; Jin-Shiung Cheng; Chun-Peng Liu; Yuk-Keung Lo; Kang-Ju Chou; Kam-Chung Lee; Wei-Chung Chen; Ih-Sheng Chen (Archives of Toxicology, 2002)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

The Heterogeneity in Risk Factors of Lung Cancer and the Difference of Histologic Distribution between Genders in Taiwan - Chien-Hung Lee; Ying-Chin Ko; Li Shu-Chuan Cheng; Ying-Chao Lin; Hsiang-Ju Lin; Ming-Shyan Huang; Jhi-Juh Huang; Eing-Long Kao; Hwei-Zu Wang (Cancer Causes & Control, 2001)

Dual action of palmitoyl trifluoromethyl ketone (PACOCF 3 ) on Ca 2+ signaling: activation of extracellular Ca 2+ influx and alteration of ATP- and bradykinin-induced Ca 2+ responses in Madin Darby canine kidney cells - Chung-Ren Jan; Kang-Ju Chou; Kam Chung Lee; Jue-Long Wang; Li-Ling Tseng; Jin-Shiung Cheng; Wei-Chuan Chen (Archives of Toxicology, 2000)